Determining fine‐scale migratory connectivity and habitat selection for a migratory songbird by using new GPS technology. (23rd January 2017) - Fraser, K. C.; Shave, A.; Savage, A.; Ritchie, A.; Bell, K.; Siegrist, J.; Ray, J. D.; Applegate, K.; Pearman, M.
Abstract : Migratory aerial insectivores are among the fastest declining avian groups, but our understanding of these trends has been limited by poor knowledge of migratory connectivity and the identification of critical habitat across the vast distances they travel annually. Using new, archival GPS loggers, we tracked individual purple martins Progne subis from breeding colonies across North America to determine precise (< > 10 m) locations of migratory and overwintering roost locations in South America and to test hypotheses for fine‐scale migratory connectivity and habitat use. We discovered weak migratory connectivity at the roost scale, and extensive, fine‐scale mixing of birds in the Amazon from distant (> 2000 km) breeding sites, with some individuals sharing the same roosting trees. Despite vast tracts of contiguous forest in this region, birds occupied a much more limited habitat, with most (56%) roosts occurring on small habitat islands that were strongly associated with water. Only 17% of these roosts were in current protected areas. These data reflect a critical advance in our ability to remotely determine precise migratory connectivity and habitat selection across vast spatial scales, enhancing our understanding of population dynamics and enabling more effective conservation of species at risk.